Performance evaluation of bitumen modified with styrene-isoprene-styrene and crumb rubber compound - Kok, Baha Vural; Yalcin, Beyza Furtana; Yilmaz, Mehmet; Yalcin, Erkut (Elsevier Sci Ltd, 2022)
Modifying bitumen with polymers has become inevitable to achieve resistance to severe traffic and environ-mental conditions. Researchers have focused on using modifiers with low-cost additives, such as crumb rubber (CR) obtained from waste vehicle tires, to enhance the efficiency of polymer modification. The present study investigated the effects of using styrene-isoprene-styrene (SIS) alone and in combination with CR on conven-tional and rheological properties of bitumen. To this end, viscosity, softening point, penetration, bending beam rheometer (BBR), and dynamic shear rheometer (DSR) tests were conducted. Elastic properties and performance grading were evaluated by the multi-stress creep recovery (MSCR) test. The use of 3% SIS with 7% CR gave one degree higher high-temperature performance level and 15% lower low-temperature stiffness than 6% SIS modification. It also provided 2.5 times lower non recoverable creep compliance and 1.5 times higher percent recovery than 6% SIS modification at 64 degrees C. The combined use of SIS and CR provided satisfactory performance under low-and high-temperature conditions and ensured a cost-effective solution when compared to the use of SIS polymer alone. Although SIS and CR modified binders exhibited satisfactory rutting resistance and elastic properties, the percent-difference criterion significantly restricted their high-temperature performance grade. According to this criterion, modification makes the binders suitable for extremely heavy traffic conditions without changing the resistance against temperature. Furthermore, it was determined that the estimated soft-ening point, viscosity and rutting parameter values as a function of SIS and CR contents are highly compatible with the experimental results.
Keywords: CR; SIS; Bitumen; Modification; Rheological properties; Multi stress creep recovery